The effects of mental health training program on stress, anxiety, and depression during pregnancy - Zahra Akbarian; Shahnaz Kohan; Hamid Nasiri; Soheila Ehsanpour (Wolters Kluwer Medknow Publications, 2018)
Background: The process of becoming a mother is considered as an enjoyable and evolutionary event of women's life. However, due to physical and mental changes, it can be associated with some degree of stress and anxiety that may lead to mental health problems. This study aimed to compare the effects of mental health training during pregnancy on stress, anxiety, and depression between two groups of couples and pregnant women. Materials and Methods: This randomized clinical trial was conducted on 120 pregnant women referring to health centers in Isfahan, Iran, from September to February 2016. The participants were randomly divided into three groups: couples (with the partner present), pregnant women (without the partner present), and control group (routine care). After completing the pretest, the intervention groups received four sessions of pregnancy mental health training. Data were collected using the Depression, Anxiety, and Stress Scales (DASS-42) and a demographic characteristics form. The collected data were analyzed using Statistical Package for the Social Sciences software. Results: Before the intervention, no statistical difference was observed among the three groups in the mean scores of stress, anxiety, and depression. The mean score of depression, anxiety, and stress decreased significantly in the intervention groups 2 weeks after the intervention respectively (F=5.84, p=0.004), (F=14.76, p < 0.001) and (F=11.98, p < 0.001). No significant difference was observed between the couples and pregnant women groups in terms of depression (p = 0.140). Conclusions: The results of this study showed that mental health training for pregnant women, especially with the presence of the partner, is a useful intervention in preventing stress, anxiety, and depression.